Experimental fire increases soil carbon dioxide efflux in a grassland long‐term multifactor global change experiment. (9th November 2016) - Strong, Aaron L.; Johnson, Tera P.; Chiariello, Nona R.; Field, Christopher B.
Abstract: Numerous studies have demonstrated that soil respiration rates increase under experimental warming, although the long‐term, multiyear dynamics of this feedback are not well constrained. Less is known about the effects of single, punctuated events in combination with other longer‐duration anthropogenic influences on the dynamics of soil carbon (C) loss. In 2012 and 2013, we assessed the effects of decadal‐scale anthropogenic global change – warming, increased nitrogen (N) deposition, elevated carbon dioxide (CO2 ), and increased precipitation – on soil respiration rates in an annual‐dominated Mediterranean grassland. We also investigated how controlled fire and an artificial wet‐up event, in combination with exposure to the longer‐duration anthropogenic global change factors, influenced the dynamics of C cycling in this system. Decade‐duration surface soil warming (1–2 °C) had no effect on soil respiration rates, while +N addition and elevated CO2 concentrations increased growing‐season soil CO2 efflux rates by increasing annual aboveground net primary production (NPP) and belowground fine root production, respectively. Low‐intensity experimental fire significantly elevated soil CO2 efflux rates in the next growing season. Based on mixed‐effects modeling and structural equation modeling, low‐intensity fire increased growing‐season soil respiration rates through a combination of three mechanisms: large increases in soil temperature (3–5 °C), significant increases in fine root production, and elevated aboveground NPP. Our study shows that in ecosystems where soil respiration has acclimated to moderate warming, further increases in soil temperature can stimulate greater soil CO2 efflux. We also demonstrate that punctuated short‐duration events such as fire can influence soil C dynamics with implications for both the parameterization of earth system models (ESMs) and the implementation of climate change mitigation policies that involve land‐sector C accounting.